Characterization, Function, and Transcriptional Profiling Analysis of 3-Hydroxy-3-methylglutaryl-CoA Synthase Gene (GbHMGS1) towards Stresses and Exogenous Hormone Treatments in Ginkgo biloba - Xiangxiang Meng; Qiling Song; Jiabao Ye; Lanlan Wang; Feng Xu (Molecules, 2017)
3-Hydroxy-3-methylglutaryl-CoA synthase (HMGS) is one of the rate-limiting enzymes in the mevalonate pathway as it catalyzes the condensation of acetoacetyl-CoA to form 3-hydroxy-3-methylglutaryl-CoA. In this study, A HMGS gene (designated as GbHMGS1) was cloned from Ginkgo biloba for the first time. GbHMGS1 contained a 1422-bp open-reading frame encoding 474 amino acids. Comparative and bioinformatics analysis revealed that GbHMGS1 was extensively homologous to HMGSs from other plant species. Phylogenetic analysis indicated that the GbHMGS1 belonged to the plant HMGS superfamily, sharing a common evolutionary ancestor with other HMGSs, and had a further relationship with other gymnosperm species. The yeast complement assay of GbHMGS1 in HMGS-deficient Saccharomyces cerevisiae strain YSC6274 demonstrated that GbHMGS1 gene encodes a functional HMGS enzyme. The recombinant protein of GbHMGS1 was successfully expressed in E. coli. The in vitro enzyme activity assay showed that the kcat and Km values of GbHMGS1 were 195.4 min−1 and 689 μM, respectively. GbHMGS1 was constitutively expressed in all tested tissues, including the roots, stems, leaves, female flowers, male flowers and fruits. The transcript accumulation for GbHMGS1 was highest in the leaves. Expression profiling analyses revealed that GbHMGS1 expression was induced by abiotic stresses (ultraviolet B and cold) and hormone treatments (salicylic acid, methyl jasmonate, and ethephon) in G. biloba, indicating that GbHMGS1 gene was involved in the response to environmental stresses and plant hormones.